2013
DOI: 10.1007/s10238-013-0252-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of methotrexate on oxidative stress and apoptosis markers in psoriatic patients

Abstract: Methotrexate (MTX), a cytotoxic chemotherapeutic agent, is considered an effective drug in the treatment of psoriasis. The aim of this study was to find out whether the effect of MTX treatment in psoriasis is due to oxidative stress-induced apoptosis. Psoriasis vulgaris patients (58 in number) were recruited for this study. Healthy volunteers (45 in number) served as control. Samples of psoriatic patients were collected and analyzed for total reactive oxygen species (ROS), malondialdehyde (MDA) levels, nitrite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 51 publications
2
45
0
3
Order By: Relevance
“…Oxidative stress contributes to the efficacy as well as the toxicity of methotrexate treatment. Elango et al . have attributed the efficacy of methotrexate in psoriasis after 12 weeks’ treatment to its induction of oxidative stress‐induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress contributes to the efficacy as well as the toxicity of methotrexate treatment. Elango et al . have attributed the efficacy of methotrexate in psoriasis after 12 weeks’ treatment to its induction of oxidative stress‐induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress contributes to the efficacy as well as the toxicity of methotrexate treatment. Elango et al 24 have attributed difference in oxidative stress markers after 8 weeks methotrexate therapy, suggesting that long-term treatment with its higher cumulative doses might result in increased oxidative stress. In the present study, treatment with methotrexate lowered the oxidative stress parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of most previous investigations are in agreement with the findings of the present study. In a study by Elango et al , 16 plasma MDA was significantly increased (p<0.001) and the activities of plasma SOD, TAC, and serum CAT levels decreased (but not significant) after MTX treatment in psoriasis patients. WANG et al , 7 in their study, demonstrated that PPE and black bean peel extract, particularly a combination of both can inhibit the pancreas damage due to OS resulting in ameliorating hyperglycemia.…”
Section: Resultsmentioning
confidence: 89%
“…Increased formation and accumulation in tissues of reactive oxygen species (ROS), reactive molecules and free radicals cause overstress and failure in functioning of antioxidant defence (AOD) having the minimum potential with formation of oxidative stress in connective tissue [16].…”
Section: Subject and Methods Of Researchmentioning
confidence: 99%